Location and distribution of the light chains in clathrin trimers. - Kirchhausen, T (1983)
Mouse monoclonal antibodies have been made that are specific for one of the light chains (LC-A) of calf brain clathrin. The determinant they recognize has been mapped by immunoelectron microscopy and shown to lie near the center of a clathrin trimer. Quantitative immunoprecipitation experiments with one of the monoclonal antibodies suggests that, despite the overall 1:2 stoichiometry, the light chain composition of an individual clathrin trimer is nearly random.